2020
DOI: 10.37358/mp.20.3.5398
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Terephthalate Degradation by Microalga Chlorella vulgaris Along with Pretreatment

Abstract: The current research explored the potential of microalgal species Chlorella vulgaris and Pretreatment to remediate plastic waste. It was concluded from the results that Pretreatment had a marked effect on the cracking and alteration of plastic polymer, which helped to grow microbial species on the cracked surface as evident by Compound Microscopy (CM), Scanning Electron Microscopy (SEM), and Fourier Transformed Infrared Spectroscopy (FTIR) analysis. FTIR data also supported the notion that in the absence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Also, the increase in inhibition with the increase in MPs concentration was least expressed in the case of PET. Recent researches [ 43 , 44 , 45 ] have confirmed that some microalgae can produce PET hydrolyzing enzymes called PETases and use PET as substrate. Although it is difficult to claim that this was the case in our experiment without performing a detailed analysis, especially when dealing with a 3-day exposure period, this assumption cannot be dismissed.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the increase in inhibition with the increase in MPs concentration was least expressed in the case of PET. Recent researches [ 43 , 44 , 45 ] have confirmed that some microalgae can produce PET hydrolyzing enzymes called PETases and use PET as substrate. Although it is difficult to claim that this was the case in our experiment without performing a detailed analysis, especially when dealing with a 3-day exposure period, this assumption cannot be dismissed.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1 , depolymerization of PET is postulated to involve a form of glycolysis reaction due to the presence of glycerol within the ternary DES [ 15 ]. It is also known that a quaternary ammonium compound, such as ChCl and DES itself, could act as a catalyst in mild glycolysis [ 7 , 8 , 15 , 26 ]. Simultaneously, the H-bond action between glycerol and urea is expected to change the charge density of the hydroxyl (OH) group in glycerol and increase the electronegativity of the oxygen atom in the glycerol OH group.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, new combinations of physiochemical treatment techniques have been applied to overcome existing hindrances to biodepolymerization [ 25 ]. For instance, Falah et al [ 26 ] proposed several sequential physiochemical treatments, including ultraviolet, high temperature, and nitric acid solvent treatment, prior to exposing PET for enzymatic degradation. The authors observed the development of cracks on the PET surface after treatment, which led to some enhancement in the enzymatic degradation of PET.…”
Section: Introductionmentioning
confidence: 99%
“…Interlevel interactions in a mixed community of microalgae and bacteria have a large impact on system resilience ( Sörenson et al, 2021 ). The potential of the microalgal species Chlorella vulgaris with pretreatment, marked by its effectiveness in cracking and changing polymers, aids the growth of microorganisms on fractured surfaces ( Falah et al, 2020 ). They found that the microbial species could produce the biodegradation products found in PET, such as alkane esters, fatty acids, benzoic acid, and aromatics, and the most toxic biodegradation product is bis(2-ethyl hexyl phthalate).…”
Section: Microbial Enzymes: a Potential Solution For Green Recyclingmentioning
confidence: 99%